A Comprehensive Approach to Disentangle the Effect of Cerebellar Damage on Physical Disability in Multiple Sclerosis - Ruggieri, Serena; Bharti, Komal; Prosperini, Luca; Giannì, Costanza; Petsas, Nikolaos; Tommasin, Silvia; Giglio, Laura De; Pozzilli, Carlo; Pantano, Patrizia (Frontiers in Neurology, 2020)
Cerebellar damage occurs frequently in Multiple Sclerosis (MS) patients, with a wide exhibition of symptoms particularly as impairments of balance and gait. Recent studies implementing new post processing MRI techniques showed how cerebellar sub-regional atrophy provide an explanation of disability in MS. The aim of this work was to evaluate the relationship between quantitative measures of physical disability, cerebellar sub-regional atrophy and cerebellar peduncle disruption. Forty-nine multiple sclerosis patients and 32 healthy subjects as controls (HS) underwent a 3T MRI including 3D T1-weighted and diffusion tensor images. Patients underwent static posturography to calculate the body’s center of pressure displacement (COP), Expanded Disability Status Scale (EDSS) and 25-foot walking test (25-FWT). Cerebellar lobular volumes were automatically calculated using the Spatially Unbiased Infratentorial Toolbox. Tract based spatial statistics (TBSS) in FSL was used to process DTI Fit generated fractional anisotropy (FA) maps to assess structural connectivity of cerebellar peduncles. Stepwise multivariate linear regression analyses were used to explore relationships between variables. Cerebellar volumes (anterior and posterior, as well as lobular volumes from I to X) were significantly lower in patients with MS than HS (p<0.05). FA in all cerebellar peduncles was lower in MS patients than in HS (p<0.05). EDSS and 25-FWT showed an association with atrophy of lobule VIIIb (β=-0.37, p<0.01, β=-0.45 p<0.001 respectively) COP measures inversely correlated with volume of lobule I-IV (β =-0.37, p<0.01, β =-0.36, p<0.01). Lower FA in the three cerebellar peduncles of MS patients positively correlated with cerebellar lobular volumes. Our findings show how sensorimotor cerebellum atrophy and disruption of both afferent and efferent cerebellar connections contribute to physical disability in MS patients.